Faktor-Faktor yang Mempengaruhi Perilaku Ibu Rumah Tangga Berbelanja di Supermarket - Didit Darmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The retail industry is a highly competitively oriented market. For the consumer industry to survive, it should have the strength to compete and it focusing on consumer behavior is a primary objective. The main objective of this case study is therefore to gather understanding and discover the shopping behavior of housewives in supermarkets. This research design is a qualitative case study. It is a cross-sectional study that conducted once using the tool of one-on-one in-depth interviews. The main purpose of this study is to gather understanding and discovery of housewives' shopping behavior in supermarkets. The target participants are women who are housewives with the age range of 25-45 years old. The target respondents were selected based on convenience sampling. The coverage area is in Surabaya City by setting Super Indo as the supermarket visited by housewives. The sample size was set at 180 respondents who were taken 10 respondents in each outlet in Surabaya city. This study found that all the observed factors of the independent variables are stated to have a real role partially or simultaneity in forming the shopping behavior of housewives. Affordable supermarket location is the dominant factor that determines the behavior of housewives shopping at supermarkets.